Avaliação da sustentabilidade do sistema de produção do milho em assentamentos rurais no município de Simão Dias-SE, utilizando o método ISA - Silva, Crislaine Santos da (2018)
Agriculture is the main form of interaction between the human with the nature and has been caused the greatest changes in the environment and, consequently, environmental impacts. And because of the complexity of the agro-ecosystem of rural properties, mainly focused on the production of corn that needs to employ technology to improve production and increase productivity, to the detriment of deforestation of the native vegetation and the intensive use of the soil that contributes to the environmental degradation, as it is the case of the Rural Settlements Eight of October and 27 of October in Simão Dias-SE. Thus, the need arises to seek ways to guarantee socioeconomic growth without harming the environment from the sustainable management of properties. Therefore, the present research aims to evaluate the socioeconomic and environmental sustainability of the aforementioned Settlements based on the Sustainability Indicators in Agroecosystems (ISA), in which 21 indicators were analyzed, covering economic and social balance sheets, management of the establishment, soil and water quality, management of production systems and the diversification of the landscape and conservation status of native vegetation. For this purpose, fieldwork was carried out in both Settlements, where a structured questionnaire was applied in Excel spreadsheet proposed by the ISA tool itself. Through the use of Multivariate Statistical Analysis, the number of producers was established for the application of the methodology and the realization of the research, soil and water analyzes were carried out in the laboratory stage, and in the cabinet stage, satellite images were collected for the generation. With the data obtained, values in the range of 0 to 1 were generated for each indicator, considering 0.7 the reference value for the good functioning of the agroecosystem and considered sustainable. So, the data generated allowed the characterization and evaluation of the socioeconomic and environmental conditions of the agricultural establishments, highlightning production systems, diversification of the agricultural landscape, natural habitats, land use and occupation, access roads, among others, and based on this detailed diagnosis, a technical adaptation plan was drawn up for the rural properties in which they described the positive aspects and weaknesses identified at the site contributed to the decision-making of the rural producer, with technical planning with integrated vision between the production systems and the conservation of the existing natural resources, in accordance with the current environmental legislation.